2021
DOI: 10.1007/s00701-021-04913-0
|View full text |Cite
|
Sign up to set email alerts
|

Decompression of the greater occipital nerve improves outcome in patients with chronic headache and neck pain — a retrospective cohort study

Abstract: Background Compression of the greater occipital nerve (GON) may contribute to chronic headache, neck pain, and migraine in a subset of patients. We aimed to evaluate whether GON decompression could reduce pain and improve quality of life in patients with occipital neuralgia and chronic headache and neck pain. Methods In this retrospective cohort study, selected patients with neck pain and headache referred to a single neurosurgical center were analyzed. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…We identified 31 studies reporting on outcomes of headache surgery without any mention of MMD. 5,10,16,[18][19][20][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]45,49,[51][52][53]55,[66][67][68][69] This is a significant body of evidence that could exist in the databases already constructed by the study authors. If so, we suspect this omission might be attributable to a lack of awareness about the preferred outcome metrics used in the neurology literature, and we hope our work will provide evidence to standardize migraine treatment metrics across both disciplines.…”
Section: Discussionmentioning
confidence: 99%
“…We identified 31 studies reporting on outcomes of headache surgery without any mention of MMD. 5,10,16,[18][19][20][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]45,49,[51][52][53]55,[66][67][68][69] This is a significant body of evidence that could exist in the databases already constructed by the study authors. If so, we suspect this omission might be attributable to a lack of awareness about the preferred outcome metrics used in the neurology literature, and we hope our work will provide evidence to standardize migraine treatment metrics across both disciplines.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic neuropathic pain affects around 7% (Szok et al, 2019) of the general population and is due to injuries or central and peripheral ‘nervous system diseases’ (AC), as in 7.4% of the analysed records. In the sample, ‘nerve compression syndromes’ (AC) are associated with chronic pain in 48.5% of cases; in particular, compression of the cervical spine is linked to the onset of persistent headache and neck pain (Eskilsson et al, 2021). In our study, it was found that an ‘imbalance of neurotransmitters, neuromodulators and receptors’ (AC) is associated with chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Success of GONB may vary depending on the techniques used, concerning the landmarks (Nair et al, 2018 ). On the other hand, in some cases, GONB does not alleviate these symptoms (Dilli et al, 2015 ; Eskilsson et al, 2021 ; Kashipazha et al, 2014 ), possibly due to anatomical variations and/or differences in the topographical location of GON (Ducic et al, 2009 ; Huanmanop et al, 2021 ; Junewicz et al, 2013 ; Natsis et al, 2006 ; Won et al, 2018 ). Although it is considered to be safe, repeated corticosteroid injections may cause complications such as Cushing's syndrome (Lavin & Workman, 2001 ) or neck muscle weakness (Ducic et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%